An Innovative Hybrid Modular Converter with H-bridge for High Voltage Direct Current Applications (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An H-bridge hybrid modular converter (HBHMC) is proposed for high-voltage direct current(HVDC) applications. It uses a wave-shaping circuit consisting of series-connected full-bridgesubmodules (FBSMs) at the output of the main H-bridge converter. For a three-phase system, threeHBHMCs are connected either in series (series-HBHMC) or in parallel (parallel-HBHMC) across thedc-link. The operating modes of HBHMC, novel modulation strategies for voltage balancing ofFBSMs, and control of HBHMC-based HVDC system are presented in this paper. A detailedcomparison between HBHMC and other hybrid topologies is performed on the basis of requirednumber of switches and capacitors. The HBHMC has the features of dc fault blocking capability,lower footprint structure, and extra degree of freedom for submodules capacitor voltage balancing.The efficacy of the HBHMC-based HVDC system for three-phase balanced and unbalanced gridconditions and its fault-tolerant capability are validated using PSCAD simulation studies.Furthermore, the feasibility of the proposed converter under normal and dc fault conditions and of theproposed capacitor voltage control scheme is validated experimentally by using a three-phase gridconnected HBHMC laboratory prototype.